Land, Landscape, and Refugees’ Identity in Krishna Dharabasi’s Saranarthi - Paudel, Maheswor (Bon Voyage, 2025)
This article examines how landscape shapes refugees’ identities in Krishna Dharabasi’s Saranarthi. It explores the impact of landscapes in Burma, Northeast India, Bhutan, and Nepal on individuals who, after residing for centuries in Burma, leave their host country in search of a place to belong. After deserting Burma, the refugees hope to find a home in their ancestors’ land. Some, upon reaching this land, smell the soil, seeking their ancestors’ footsteps and the comfort of a homeland. Others explore living opportunities in Indian locations such as Assam, Meghalaya, Manipur, Mizoram, Sikkim, and Darjeeling, or head to Bhutan, anticipating opportunities in a new location. Ironically, these refugees, marginalized by discriminatory state laws, are compelled to abandon their new locations and are eventually transported to their ancestors’ land. Drawing on scholars like Arjun Appadurai and Paul Jay, who discuss the nexus between transnational space and identity, this study scrutinizes how a literary work creates a connection between landscape and identity, particularly for transnational subjects like the refugees in Saranarthi. Based on the characters’ mobility across different locations, this paper concludes that land and landscapes are inseparable from human identity, and is more intense and engaging in refugees’ lives.